Stellung und Bedeutung der Physischen Anthropogeographie - Paffen, Karlheinz (ERDKUNDE, 1959)
Physical anthropogeography is, together with social geography, one of the youngest branches of human geography. It was founded in the 1920s by A. Penck, H. Lautensach and others as a branch of its own, though the beginnings of its different parts date back far. Phys. a. is not concerned with the general physiogeographical bases of human-geography, neither does it deal with the problem of the influence of nature on man, which is the exclusive subject of Ratzel's Anthropogeographie and the geographical environmentalism . Phys. a. is regionalism especially concerned with the anthropo-biological and anthropo-ecological qualities of natural and cultural regions of the earth. Its major problems are the following: the developmental regions of mankind (genetic phys. a.), biological population geography (including the geography of races), anthropoclimatology, medical geography, geography of alimentation, the anthropo-ecological division of the earth and finally its alimentary capacity. Phys. a. is a direct link between human geography and biogeography and should be connected to social geography, thus forming a population geography in the most comprehensive sense of the term.